INFORMATION FLOW OF THE PRESENT TIME AND ITS INFLUENCE ON ADOLESCENT PSYCHOLOGY ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2023)
The article describes the rapid penetration and development of computers networks in modern human life and activity, their special role in solving social, economic and even political problems of society, as well as the impact of pedagogical and psychological characteristics, knowledge, worldview. information about.